“Welcome to the desert of the real” : uma proposta teóricometodológica de cartografia de franquia de cultura pop a partir de matrix - Becko, Larissa Tamborindenguy (Universidade do Vale do Rio dos Sinos, 2022)
The main objective of this work is to map and analyze the dynamics and logic of pop culture franchises based on the Matrix franchise. From the understanding of the franchise as a fictional universe, we sought to outline and discuss the characteristics that make up these media systems and their functioning as a business model centered on consumption and on the engagement of fans and consumers. Using cartography and grounded theory as a methodological arrangement, an analysis was carried out that included posts made on content portals about the release of the feature film Matrix Resurrections (2021) as well as interviews and a focus group with fans and content producers involved with the fictional universe with the objective of verifying the new configurations of the franchise in the contemporary context. As a result, the thesis proposes the understanding of pop culture franchises as complex sets of elements, actors, structures, flows, etc. that are established from three main dimensions: media, marketing and consumption.
Keywords: Franquia; Cultura pop; Consumo; Fãs; Fandom; Matrix; Franchise; Pop culture; Consumption; Fans; ACCNPQ::Ciências Sociais Aplicadas::Comunicação